E-Readiness Dinas Tenaga Kerja Kota Bandung Dalam Penyelenggaraan Pelayanan Bursa Kerja Online Melalui Aplikasi BIMMA (Bandung Integrated Manpower Management Applications) - M. Andri Julianto P; Slamet Usman Ismanto; Dedi Sukarno (JANE - Jurnal Administrasi Negara, 2022)
This research was distributed by the existence of the phenomenon of changing job fair services that go an offline system to an online system and not achieving the three performance targets in the implementation of online job fair services through the BIMMA applicatio.. The purpose of this research is to find out how the e-Readiness of the Bandung City Manpower Service in organizing online job fair market services through the BIMMA application. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques through observation, interviews, and documentation. The validity technique is done by triangulating sources from the results of interviews and documentation studies.                                                                                                                                   The results of this research showed that the e-Readiness of the Bandung City Manpower Service in providing online job fair market services through the BIMMA application was considered ready on the grounds that there were 5 (five) factors that had been fulfilled and 1 (one) factor that had not been fulfilled related to the factors affecting e-Readiness of the Bandung City Manpower Office. These factors can be seen from the availability of telecommunication infrastructure needs, the availability of connectivity and the use of IT by the government because the facilities have been used and maintained properly, the funds and budget are available according to their needs, the law that regulates online job fair market services is available, and there has been a paradigm shift by government employees. Suggestions for this problem are the Bandung City Manpower Service needs to pay attention to the needs of facilities and infrastructure, refinement of human resource planning in the division of tasks, re-analyze the workload and quantity of employees, take decisive action in carrying out tasks issuing sanctions, and increasing the intensity of discussion and joint evaluation among employees. Penelitian ini dilatabelakangi oleh adanya fenomena perubahan pelayanan bursa kerja dari sistem offline menjadi sistem online serta tidak tercapainya tiga capaian kinerja sasaran dalam pelaksanaan pelayanan bursa kerja online melalui aplikasi BIMMA. Tujuan dari penelitian ini untuk mengetahui bagaimana e-Readiness Dinas Tenaga Kerja Kota Bandung dalam penyelenggaraan pelayanan bursa kerja online melalui aplikasi BIMMA. Metode dalam penelitian ini adalah metode kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Teknik keabsahan dilakukan dengan triangulasi sumber dari hasil wawancara dan studi dokumentasi.                             Hasil penelitian menunjukan bahwa e-Readiness Dinas Tenaga Kerja Kota Bandung dalam penyelenggaraan pelayanan bursa kerja online melalui aplikasi BIMMA dinilai sudah siap dengan alasan telah terdapat 5 (lima) faktor yang sudah terpenuhi dan 1 (satu) faktor yang belum terpenuhi terkait dengan faktor yang mempengaruhi e-Readiness Dinas Tenaga Kerja Kota Bandung. Faktor-faktor tersebut yaitu bisa dilihat dengan sudah tersedianya kebutuhan infrasturktur telekomunikasi, sudah baiknya tingkat konektivitas dan penggunaan TI oleh pemerintah karena sarana dan prasaran telah dimanfaatkan dan dirawat dengan baik, sudah tersedianya dana dan anggaran sesuai dengan kebutuhannya, sudah tersedianya perangkat hukum yang mengatur tentang pelayanan bursa kerja online, dan sudah baiknya perubahan paradigma oleh para pegawai. Saran yang diajukan atas penelitian ini ialah Dinas Tenaga Kerja Kota Bandung perlu untuk memperhatikan kebutuhan sarana dan prasarana, melakukan perencanaan SDM dalam melakukan pembagian tugas, menganalisis kembali antara beban kerja dan kuantitas pegawai, melakukan tindakan yang tegas dalam menjalankan sanksi, dan meningkatkan intensitas diskusi dan evaluasi bersama antar pegawai.